Positive Correlation Between Serum Interleukin‐1β and State Anger in Rugby Athletes. Issue 2 (3rd December 2012) - Pesce, Mirko; Speranza, Lorenza; Franceschelli, Sara; Ialenti, Valentina; Iezzi, Irene; Patruno, Antonia; Rizzuto, Alessia; Robazza, Claudio; De Lutiis, Maria Anna; Felaco, Mario; Grilli, Alfredo
<x xml:space="preserve">Abstract</x> Recently, several studies reported a relationship between immune system activation and anger expression. Consequently, the aim of this study was to explore immunitary molecular mechanisms that potentially underlie anger expression. To this end, we applied the Frustration—Aggression Theory in a contact sport model, utilizing the nearing of sporting events to trigger anger feelings. In parallel, we evaluated the activation of immune system at mRNA levels. We enrolled 20 amateur rugby players (age ± SD, 27.2 ± 4.5) who underwent psychological assessment to evaluate anger, with the State‐Trait Anger Expression Inventory‐2 (STAXI‐2), before rugby matches; at the same time blood samples were taken to analyze the variations of gene expression by microarray. During the 2 hr before each game, a significant increase was verified in the Rage State (RS) score compared to the score ascertained 72 hr before. At the same time, we found modulation in expression profile, in particular increased expression of gene that encodes interleukin l‐β (IL‐1β). In a regression analysis, RS score was related to IL‐1β, and the potential risk factors age, body mass index, smoking, and drinking. The levels of cytokine were positively and independently related to RS score. Our results suggest that the nearing of sporting event can trigger anger state feelings and activate immune system in rugby players. We propose the IL‐1β as a potential biological marker of anger. However, further research is necessary to clarify the correlation between cytokine and anger. Aggr. Behav. 39 :141‐148, 2013. © 2012 Wiley Periodicals, Inc.